Evaluation of Special Economic Zone Development Policies and Strategies with the SWOT Balanced Scorecard Approach - Akbar, Syahrir; Kurniawan, Gevin (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
Indonesia has built many Special Economic Zones (SEZs) to strengthen the country's economy. However, often, the development does not provide maximum results. This study aims to evaluate the policies and strategies for developing Special Economic Zones (SEZs) in Indonesia using the SWOT and Balanced Scorecard (BSC) analysis approaches. The research method uses qualitative data collection techniques through literature studies and document analysis. The SWOT analysis identifies internal factors in the form of strengths and weaknesses and external factors consisting of opportunities and threats. The SWOT analysis results are integrated into the BSC framework, consisting of four perspectives: finance, customers, internal processes, and learning and growth. Each perspective has four strategies and a measurable Key Performance Index (KPI). This study produces comprehensive strategic recommendations for SEZ development that include optimizing investment incentives, improving investor services, strengthening institutional coordination, and developing HR competencies. The implementation of this strategy is expected to increase the competitiveness of Indonesian SEZs at the regional and global levels. Keywords: Evaluation, Special Economic Zones, SWOT, Balanced Scorecard